Pemberdayaan Komunitas Kelompok Tani Melalui Program Pelatihan Penanaman Kopi Dan Strategi Pengembangan Agrobisnis Kopi Robusta Di Kecamatan Ulubelu Kabupaten Tanggamus - Dyah Anggraeni; Tika Leoni Putri; Ainun Silvi Asya (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2024)
ABSTRACTOne type of coffee that grows and thrives in the Ulubelu area, particularly in Gunung Sari Village, Ulubelu District, Tanggamus Regency, is Robusta coffee. The Robusta coffee found in Ulubelu is one of the region's leading commodities that must be developed and preserved. The purpose of this community service activity is to assist farmer groups in the Ulubelu District to innovate in agribusiness development by utilizing coffee commodity products from upstream to downstream and turning them into high-quality sources of livelihood. The method used in this community service program is descriptive qualitative, carried out through discussions, counseling, training, and direct evaluation with coffee farmers and entrepreneurs. The results of the workshop training successfully improved the skills of the farmer group members in providing organic fertilizers and in environmentally friendly pest and disease control for coffee plants. In addition, the service team provided training on agribusiness marketing development strategies, which enhanced the farmers’ skills in processing their harvests, thereby increasing the product's selling value and serving as a higher source of income for the development of community-based MSMEs. This was done by evaluating the progress of coffee cultivation and post-harvest handling practices. Keywords: Training; Farmer Groups of Ulubelu District; Robusta Coffee.